2014
DOI: 10.1260/1756-8293.6.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Lift and Drag Characteristics of a Typical MAV under Propeller Induced Flow

Abstract: Experiments were conducted on a micro air vehicle (MAV) model in a low speed wind tunnel to study the actual lift and drag experienced by the model under propeller induced flow by separating out the thrust force generated by the propeller by decoupling the motor-propeller from the model and mounting it on a second arrangement with minimal flow interference. Tests were conducted on the model at actual flight conditions -at a freestream velocity of 9 m/s (Re = 135000 based on root chord) with the propeller runni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…11 Similarly, experiments at Reynolds number 135,000 with motor rotation in the range of 8000-10,000 r/min with 300 mm wingspan model showed an increase of C L at a higher AoA and increase of C D with the propulsive flow. 12 The effects of propeller induced flow on C L and C D further increases with an increase in the speed of motor rotation. Similarly, the increase of lift, drag, and stall AoA with increasing slipstream to free stream velocity ratio is observed during wind test on a model with a wingspan of 252.0 mm and a chord length of 142.6 mm with a propeller diameter of 5.5 inches in the velocity range of 5-15 m/s.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…11 Similarly, experiments at Reynolds number 135,000 with motor rotation in the range of 8000-10,000 r/min with 300 mm wingspan model showed an increase of C L at a higher AoA and increase of C D with the propulsive flow. 12 The effects of propeller induced flow on C L and C D further increases with an increase in the speed of motor rotation. Similarly, the increase of lift, drag, and stall AoA with increasing slipstream to free stream velocity ratio is observed during wind test on a model with a wingspan of 252.0 mm and a chord length of 142.6 mm with a propeller diameter of 5.5 inches in the velocity range of 5-15 m/s.…”
Section: Introductionmentioning
confidence: 97%
“…8 The size of the propeller dimension to the wing dimension is comparable in the case of propeller-driven MAV; hence, the effect of the propeller-induced flow on the overall aerodynamics is quite significant as it influences the flow transition, 9 flow separation, flow reattachment and formation of laminar separation bubbles. 10 The important parameters that are affected by the propulsive forces are stall angle of attack (AoA), 11 lift coefficient ( C L ), and drag coefficient (CD), 12 the slope of lift versus AoA curve, 13 LD ratio, 14,15 pitching moment, 16 etc. Propeller flow also influences the transition from laminar flow to turbulent flow.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a conventional aircraft modeling techniques that do not take into account of propeller wake are inadequate to model the aerodynamic forces acting on MAV. The aerodynamic effects of propeller flow on MAV and small UAV are studied in [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The influence of propeller wake on the lift, drag and wing stall characteristics is reported in [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…12,13 The use of small distributed propellers upstream of the wing leads to an increase in aerodynamic lift. [14][15][16][17] The performance benefits of these wings are directly applicable to the takeoff and landing flight regimes due to a higher achievable lift curve slope and C L max . However, recent computational studies have shown the increase in aerodynamic drag of the wing due to slipstreams.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent computational studies have shown the increase in aerodynamic drag of the wing due to slipstreams. 16,17 Wingtip mounted propellers which improve the aerodynamic efficiency of the wing 18,19 can be used to provide thrust during cruise with the inbound propeller shut and folded. 16 Preliminary wing design and aircraft performance tools for V/STOL aircraft with distributed propeller system such as those developed by Bronz et al 20 require better theory to understand the aerodynamic interaction between a propeller and a wing.…”
Section: Introductionmentioning
confidence: 99%